2017
DOI: 10.5455/msm.2017.29.196-200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pressure Ulcer and Nutritional Factors Affecting Wound Closure Success in Thailand

Abstract: Introduction:The authors aimed to estimate the prevalence of pressure ulcers and to explore the nutritional effects of the prognostic factors on successful pressure ulcer closure in a public tertiary care hospital in Thailand.Patients and Methods:The study was a retrospective cohort analysis of seven-year census (2008 - 2014) at Surin hospital in Thailand. There were 424 of total 240,826 patients aged over than 15 years admitted to surgery, orthopedics and medicine wards during the study period with documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Magny et al 29 found that low albumin level was associated with PU development. Auiwattanakul et al 4 also suggested that the nutrition factor is an establishing predictor for pressure wound closure, and every 1‐gm/dL increase in serum albumin increases wound closure by 21%. In our study, albumin was only monitored regularly in ICU patients, and low albumin levels were associated with PU development in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magny et al 29 found that low albumin level was associated with PU development. Auiwattanakul et al 4 also suggested that the nutrition factor is an establishing predictor for pressure wound closure, and every 1‐gm/dL increase in serum albumin increases wound closure by 21%. In our study, albumin was only monitored regularly in ICU patients, and low albumin levels were associated with PU development in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…They can be associated with pain, increased risk of infection, and need for additional surgical procedures. They also increase the risk of prolonged length of hospital stay, morbidity, and mortality 3,4 . Additionally, it is estimated that 11 billion USD per year is spent for the total cost of hospital‐acquired PU (HAPU) in the USA, and this is not reimbursable 5 …”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Keys et al [8] found that albumin levels below 3.5 g/dL were associated with ulcer recurrence within 1 year, suggesting that malnutrition should be corrected with high-protein diets and peripheral amino acid infusions, and nutritional markers, including albumin and prealbumin, should be moni-tored as a means of directing treatment [2]. In another study, the caloric deficit per day was higher in patients with successful pressure ulcer closure, although this finding did not achieve statistical significance [9].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 57 studies reported data on clinical outcomes in patients with hospital malnutrition (Table 3) [19,20,22,24e27,29,30, 33,34,36,37,40e46,48,50e54,56e61,63,65e70,72e74,78,80e83, 96,103e110]. Overall, the studies demonstrated a significant association between poor nutrition status and an increased risk of clinical complications, including infection [50,51,53,56,60,63,103], pressure ulcers [87,106], and fractures [104], as well as pulmonary [67,73], renal [67], and hepatic complications [67]. Studies in surgical patients showed an increased risk of postoperative complications [48,52,54,56,58,60,66,67,72e74,83], including surgical site infection [56,60], bleeding [67], pneumonia [73], delayed wound healing [54,67], and delayed ambulation [72].…”
Section: Clinical Consequencesmentioning
confidence: 99%